Parotid Gland Dose in Intensity-Modulated Radiotherapy for Head and Neck Cancer: Is What You Plan What You Get? - O'Daniel, Jennifer C.; Garden, Adam S.; Schwartz, David L.; Wang, He; Ang, Kian K.; Ahamad, Anesa; Rosenthal, David I.; Morrison, William H.; Asper, Joshua A.; Zhang, Lifei; Tung, Shih-Ming; Mohan, Radhe; et al. (International journal of radiation oncology, biology, physics, 2007)
To quantify the differences between planned and delivered parotid gland and target doses, and to assess the benefits of daily bone alignment for head and neck cancer patients treated with intensity-modulated radiotherapy (IMRT). Eleven head and neck cancer patients received two CT scans per week with an in-room CT scanner over the course of their radiotherapy. The clinical IMRT plans, designed with 3-mm to 4-mm planning margins, were recalculated on the repeat CT images. The plans were aligned using the actual treatment isocenter marked with radiopaque markers (BB) and bone alignment to the cervical vertebrae to simulate image-guided setup. In-house deformable image registration software was used to map daily dose distributions to the original treatment plan and to calculate a cumulative delivered dose distribution for each patient. Using conventional BB alignment led to increases in the parotid gland mean dose above the planned dose by 5 to 7 Gy in 45% of the patients (median, 3.0 Gy ipsilateral, p = 0.026; median, 1.0 Gy contralateral, p = 0.016). Use of bone alignment led to reductions relative to BB alignment in 91% of patients (median, 2 Gy; range, 0.3–8.3 Gy; 15 of 22 parotids improved). However, the parotid dose from bone alignment was still greater than planned (median, 1.0 Gy, p = 0.007). Neither approach affected tumor dose coverage. With conventional BB alignment, the parotid gland mean dose was significantly increased above the planned mean dose. Using daily bone alignment reduced the parotid dose compared with BB alignment in almost all patients. A 3- to 4-mm planning margin was adequate for tumor dose coverage.